A study of an experimental formulation for development of improved dental cements - Zidan, Ahmed Zaki; Habib, Ahmed Nour ElDin; AbouTabi, Zohair Mohammed (2008)
This study has been conducted in an attempt to develop newly formulated powders, which can react with sterile distilled water to produce suitable cements for dental use. Three experimental powders have been formulated Powder a consisted of white portland cement powder with 10% calcium chloride
Supervisors: Ahmed Nour Eldin Habib, Zohair Mohammed Aboutabi
Thesis (Ph.D.) - Cairo University, Faculty of Oral and Dental Medicine, 2008.
Text in English, abstracts in English & Arabic.
Keywords: Dental Cement; Dental Material; Mineral trioxide aggregate. -- Portland cements